2017
DOI: 10.4314/ajoh.v7i1.162230
|View full text |Cite
|
Sign up to set email alerts
|

Self perceived satisfaction with dental appearance and desired treatment to improve aesthetics

Abstract: with the treatment. Treatments which improve dental aesthetics have been found to improve quality of life and 8 psychological status. Patients who have interest in improving their dental appearance have been found to frequently demand for tooth whitening treatments, 9 anterior teeth restoration and orthodontic treatment. There may be possible differences in aesthetic perception between clinician and patient which could create problems during treatment if not properly 10 recognized. Clinicians must therefore be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…This was found to be contrasting from the study by Afshar et al 16 in which participant aged 21-25 years were more dissatisfi ed with their teeth colour. People with higher education are more satisfi ed with their teeth colour which is similar to the study done by Vallitu et al 8 and Xiao et al 27 Higher the education more the satisfaction with the teeth colour may attributed to higher confi dence level and higher selfesteem level. 4,26 Malocclusion has prominent role in the anterior aesthetic.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This was found to be contrasting from the study by Afshar et al 16 in which participant aged 21-25 years were more dissatisfi ed with their teeth colour. People with higher education are more satisfi ed with their teeth colour which is similar to the study done by Vallitu et al 8 and Xiao et al 27 Higher the education more the satisfaction with the teeth colour may attributed to higher confi dence level and higher selfesteem level. 4,26 Malocclusion has prominent role in the anterior aesthetic.…”
Section: Discussionsupporting
confidence: 86%
“…16 Less than quarter of the participants claimed to have caries in front teeth (19.19%), unaesthetic fi lling (11.74%) and fracture in their anterior teeth(20.64%) which were similar to the study done in Nigeria where caries in front teeth account for 19.7%, unaesthetic fi lling 7.4% and fracture in front teeth 21.3%. 27 The most preferred treatment in this study to improve aesthetics is tooth whitening which is the fi nding similar to the most preferred cosmetic dental treatment in Malaysia and Riyadh. 7,28 This suggests that satisfaction of anterior teeth aesthetics has strong co-relation with teeth color.…”
Section: Discussionmentioning
confidence: 80%
“…Some researchers suggested that self-perception declined with age and that older patients have fewer concerns about the esthetics of their teeth and face [19,20]. Other researchers, in contrast, reported that age had no significant effects on the perception of dental esthetics [8,21].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature is very rich with studies showing an association between the patients' satisfaction with their smile and the characteristics of the latter, in particular the size, shape, alignment, color and visibility of teeth, the gingival display, the desired treatment etc ( Van der Geld P et al, 2007;Alkhatib MN et al, 2005;Azodo C & Ogbomo A. 2014;Enabulele JE & Omo JO 2017;Isiekwe GI & Aikins EA 2019;Tin-Oo MM et al, 2011;Hassel AJ et al, 2011;Al-Zarea BK 2013). However, additional research is needed to assess these factors in the Moroccan population in order to better understand the results of our study.…”
Section: Discussionmentioning
confidence: 99%